2001
DOI: 10.1182/blood.v97.10.3283
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and efficient homing of human CD34+CD38−/lowCXCR4+stem and progenitor cells to the bone marrow and spleen of NOD/SCID and NOD/SCID/B2mnull mice

Abstract: Stem cell homing into the bone microenvironment is the first step in the initiation of marrow-derived blood cells. It is reported that human severe combined immunodeficient (SCID) repopulating cells home and accumulate rapidly, within a few hours, in the bone marrow and spleen of immunodeficient mice previously conditioned with total body irradiation. Primitive CD34 ؉ CD38 ؊/low CXCR4 ؉ cells capable of engrafting primary and secondary recipient mice selectively homed to the bone marrow and spleen, whereas CD3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
260
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(284 citation statements)
references
References 54 publications
20
260
0
4
Order By: Relevance
“…A CXCR4-negative progenitor cell line (Kasumi-1) did not display pseudoemperipolesis. The SDF-1/ CXCR4 axis and binding of a4b1 and a5b1 integrins has recently been demonstrated to be involved in the transendothelial migration of haematopoietic progenitor cells (HPC) (Mohle et al, 1998;Jo et al, 2000;Peled et al, 2000), in the rolling and arrest of HPC on vascular endothelial cells under shear flow (Peled et al, 1999b), and in human HPC mobilization and homing (Prosper et al, 1998;Peled et al, 1999a;Kollet et al, 2001). It has also been demonstrated that HSC are uniquely selective in their chemotactic responsiveness to SDF-1, suggesting that this chemokine is the key factor for homing of HSC to the marrow that cooperates with integrins, in particular a4b1 integrins (Wright et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A CXCR4-negative progenitor cell line (Kasumi-1) did not display pseudoemperipolesis. The SDF-1/ CXCR4 axis and binding of a4b1 and a5b1 integrins has recently been demonstrated to be involved in the transendothelial migration of haematopoietic progenitor cells (HPC) (Mohle et al, 1998;Jo et al, 2000;Peled et al, 2000), in the rolling and arrest of HPC on vascular endothelial cells under shear flow (Peled et al, 1999b), and in human HPC mobilization and homing (Prosper et al, 1998;Peled et al, 1999a;Kollet et al, 2001). It has also been demonstrated that HSC are uniquely selective in their chemotactic responsiveness to SDF-1, suggesting that this chemokine is the key factor for homing of HSC to the marrow that cooperates with integrins, in particular a4b1 integrins (Wright et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…During this multistep process, circulating HSC must first interact with marrow endothelial cells, followed by rolling, firm adhesion and extravasation into the haematopoietic compartment. Pretreatment of human HSC with anti-CXCR4 or anti-VLA-4 or anti-VLA-5 mAbs prevented engraftment in NOD/SCID mice (Peled et al, 1999a(Peled et al, , 2000Kollet et al, 2001), and systemic SDF-1 overexpression results in the mobilization of HSC (Hattori et al, 2001). Collectively, these observations indicate that, in vivo, a gradient of SDF-1 attracts and retains HSC within the marrow microenvironment.…”
mentioning
confidence: 94%
“…cells than MSC. Culture of CB cells in M-OST CM (OCM) and to a lesser extent MSC CM also resulted in increased frequency of cells positive for the cell-surface expression of C-X-C chemokine receptor type 4 (CxCR4) implicated in the HSPC homing to the BM (Peled et al 1999;Kollet et al 2001;Peled et al 2000). Importantly, OCM was shown to modulate the engraftment properties of expanded HSPC.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In transplanted NOD/SCID mice, homing and subsequent engraftment of human normal or AML stem cells are dependent on the expression of cell surface CXCR4 and SDF-1 produced within the murine. [9][10][11][12] In addition to controlling cell motility, SDF-1 regulates cell proliferation, induces cell cycle progression and acts as a survival factor for normal human stem cells and AML cells. [13][14][15][16] CXCR4 blockage in AML cells, using the polypeptide RCP168, enhanced chemotherapy-induced apoptosis in vitro.…”
Section: Introductionmentioning
confidence: 99%